A Study on a small scale jatropha biofuel in Cambodia to increase income generating and electricity supply in Paoy Char commune - Sopornetra, Chap (KDI School, 2011)
In Cambodia, almost 90% of the rural population is living without access to an electricity grid. Capacities to significantly expand Cambodian electricity grids in the coming years are building up at slow speed. This situation creates possibilities for Rural Electrification Enterprises to set up isolated small electricity grids and supply individual communes with electricity. The use of renewable energy such as Jatropha oil is a sustainable way to set up such a system. This paper aims to present the case study of biofuel growth in Cambodia, particularly Jatropha curcas plantation at household level given the selected location in Paoy Char commune, Phnom Srok District, Banteay Meanchey Province; to find out whether Jatropha biofuel will lead to affordable electricity for the rural population and at the same time increasing income and employment in Paoy Char commune through the extended business activities. The finding delivers adequate solid proof to realize that the scenarios of both developing Jatropha and running electricity in Paoy Cha commune are very favorable. However, the lack of markets and too low prices of Jatropha seeds are the household’s concern.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: Cambodia